2000
DOI: 10.1099/0022-1317-81-5-1211
|View full text |Cite
|
Sign up to set email alerts
|

Detection of lymphocytes productively infected with Epstein–Barr virus in non-neoplastic tonsils

Abstract: Epstein-Barr virus (EBV) persists for life in the infected host.Little is known about EBV reactivation and regulation of virus persistence in healthy individuals. We examined tonsils of chronic tonsillitis patients to detect EBV transcripts, EBV genomes and lytic proteins. LMP1 transcripts were observed in 11 of 15 specimens and BZLF1 transcripts were detected in six. Multiple copies of EBV genome equivalents per cell, and ZEBRA-and viral capsid antigen-positive cells were also detected in tonsillar lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…14 Additionally, viral proteins found in latent and replicative infection may be identified by immunohistochemical techniques. [2][3][4]13 The tonsils are considered the site of initial infection, and of viral persistence and replication. The EBV may infect the tonsils of children and become involved in recurring tonsillitis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…14 Additionally, viral proteins found in latent and replicative infection may be identified by immunohistochemical techniques. [2][3][4]13 The tonsils are considered the site of initial infection, and of viral persistence and replication. The EBV may infect the tonsils of children and become involved in recurring tonsillitis.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have suggested that the tonsils are a possible replication site for this virus. 2,3,8,13 Molecular techniques have been used often for diagnosing and monitoring patients with virus diseases. The EBV-DNA can be identified by in situ hybridization (ISH) and the polymerase chain reaction (PCR); some authors consider both equally sensitive for detecting the EBV.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations